Multidimensions of Media Multitasking and Adaptive Media Selection. - Wang, Zheng; Irwin, Matthew; Cooper, Cody; Srivastava, Jatin (Human Communication Research, 2015)
This study identifies 11 basic cognitive dimensions of media multitasking behaviors based upon resource theories. These dimensions provide a conceptual framework to help compare and synthesize media multitasking studies. In addition, using 2 empirical data sets, we examine how these cognitive dimensions interact with each other to predict choices of media multitasking behaviors in daily life in an adaptive manner to conserve limited mental resources. A systematic understanding of the multiple cognitive dimensions of media multitasking behaviors has the potential to foster theory-guided designs and more mindful selection of media tasks, technologies, and environments to curb negative consequences of media multitasking and utilize its benefits.